2017
DOI: 10.2217/imt-2016-0123
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CTLA-4 Therapy for Malignant Mesothelioma

Abstract: Immunotherapy is an emerging therapeutic strategy with a promising clinical outcome in some solid tumors, particularly metastatic melanoma. One approach to immunotherapy is immune checkpoint inhibitors, such as blockage of CTLA-4 and PD-1/PD-L1. This special report aims to describe the state of clinical trials of tremelimumab in patients with unresectable malignant mesothelioma (MM) in particular with regard to the clinical efficacy, safety and tolerability. Criticism and perspective of this treatment are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Altogether, the evidence that IGF-II is also used by cancer stem cells, besides being commonly expressed in solid cancers [166][167][168][169], supported by the findings already obtained using genetic, molecular, and cellular approaches, suggests further new hypotheses. In particular, the observation that the presence of autocrine IGF-II loops is associated with overtly malignant cancer cell lines [14,45,94,[170][171][172][173] and that IGF-II over-expression overlaps with those cancer types currently poorly responsive to immune checkpoint therapy (such as malignant mesothelioma [174][175][176], glioblastoma [177,178], and pancreatic carcinoma [179,180]) along with certain BRAF-inhibitor-treated recurring cancers [181,182] suggest that the autocrine IGF-II/IR A axis role under these circumstances should be investigated and its targeting potential experimentally vetted. Importantly, a sufficient amount of scientific evidence differentiating the biological and contextual pathological roles of the two IGF-II receptor tyrosine kinase signal transducers, namely the IGFIR and the IR A , has been produced to clear out the doubts and unmet past expectations linked to the failed strategy of IGFIR blocking [68,69].…”
Section: Targeting the Autocrine Igfii/ir A Loop In Cancer: A Furthermentioning
confidence: 99%
“…Altogether, the evidence that IGF-II is also used by cancer stem cells, besides being commonly expressed in solid cancers [166][167][168][169], supported by the findings already obtained using genetic, molecular, and cellular approaches, suggests further new hypotheses. In particular, the observation that the presence of autocrine IGF-II loops is associated with overtly malignant cancer cell lines [14,45,94,[170][171][172][173] and that IGF-II over-expression overlaps with those cancer types currently poorly responsive to immune checkpoint therapy (such as malignant mesothelioma [174][175][176], glioblastoma [177,178], and pancreatic carcinoma [179,180]) along with certain BRAF-inhibitor-treated recurring cancers [181,182] suggest that the autocrine IGF-II/IR A axis role under these circumstances should be investigated and its targeting potential experimentally vetted. Importantly, a sufficient amount of scientific evidence differentiating the biological and contextual pathological roles of the two IGF-II receptor tyrosine kinase signal transducers, namely the IGFIR and the IR A , has been produced to clear out the doubts and unmet past expectations linked to the failed strategy of IGFIR blocking [68,69].…”
Section: Targeting the Autocrine Igfii/ir A Loop In Cancer: A Furthermentioning
confidence: 99%
“…FAP has been shown to be expressed on tumour-associated fibroblasts and cancer cells, and use of human CD8+ T cells transduced with anti-FAP demonstrated growth inhibition of FAP-positive tumour cells 51 , thus providing further evidence for the role of the stroma. It has been argued that once the toxicity of the immune checkpoint inhibitors reaches acceptable levels approaches such as combination checkpoint therapy could be employed, or their role as adjuvant therapy considered 29 . However, further research is required prior to the clinic for immune checkpoint blockade in mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…There is much focus on blockage of PD-1 (programmed cell death protein 1) and CTLA-4 (cytotoxic T-lymphocyte associated protein 4) which are two key negative regulators of the immune system 28 . CTLA-4 is under particular scrutiny due to the fact that ipilimumab, another antibody against it, has been approved for the treatment of melanoma 29 . Immune checkpoint blockade in mesothelioma has been comprehensively reviewed by Marcq and colleagues 30 Tremelimumab is a monoclonal antibody against CTLA-4 (similar to ipilimumab), which is currently under investigation in clinical trials.…”
Section: Passive Immunotherapymentioning
confidence: 99%
“…Clinical trials have confirmed that tremelimumab has a certain therapeutic effect on melanoma. In addition, it was approved for the treatment of malignant mesothelioma in 2015, and approximately 52% of patients were effectively controlled, with a median survival of 10.9 months [23]. However, the therapeutic effect of tremelimumab on bladder tumors remains to be discussed.…”
Section: Immunotherapy Of Ctla-4 Inhibitors and Bladder Tumorsmentioning
confidence: 99%